Indian Consciousness in Aravind Adiga’s The White Tiger - Kerketta, Juwel; Tiwari, Om Prakash (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
This paper examines how caste, class and gender intersect to shape Indian consciousness in Aravind Adiga’s The White Tiger. Focusing on Balram Halwai’s first‑person narrative of his journey from a lower‑caste village boy to a Bangalore entrepreneur, it argues that his evolving self‑understanding is produced within, and against, India’s entrenched hierarchies and rapidly changing economic order. Through close reading of key episodes in Laxmangarh, Delhi and Bangalore, the study explores how Balram internalises and then contests normative beliefs about family loyalty, servitude, masculinity and success, revealing a consciousness marked by resentment, ambition and ethical ambivalence. Central to the analysis is the “rooster coop” metaphor, which is read as a condensed image of intersecting structures of caste subordination, class exploitation and patriarchal control that keep the poor “guarded from the inside.” By tracing how Balram both exposes and reproduces this system—ultimately embracing violence and corruption to “break out”—the paper contends that The White Tiger offers not a simple rags‑to‑riches fable but a complex representation of Indian consciousness under liberalisation. The novel thus unsettles celebratory narratives of a “shining” India by foregrounding the psychological captivity, moral compromises and fractured agency of those at the bottom of its social order.